A BIBLICAL LAZARUS: DEREGISTRATION OF A COMPANY AND THE REVIVAL OF RIGHT TO MINERALS A discussion of Palala Resources (Pty) Ltd v Minister of Mineral Resources and Energy 2016 (6) SA 121 (SCA) - Heleen van Niekerk; Shamila Mpinga (Obiter, 2018)
The notion of death and resurrection is intriguing. As part of a religious teaching, rising from the dead is often associated with an act of a deity for the salvation of humankind. Holding the ultimate power of having defeated death, the resurrected deity often has the ability to perform the miracle of commanding others to rise from the dead. For some, these religious beliefs are of the utmost importance and, frequently, take centre stage in the believer’s life. While it is generally accepted that people have the freedom to choose their religious beliefs, we should tread cautiously when the law assumes the characteristic of performing miracles. This need to tread cautiously is well illustrated in Palala Resources (Pty) Ltd v Minister of Mineral Resources and Energy 2016 (6) SA 121 (SCA) (hereinafter “Palala Resources (SCA)”). The case concerns the interpretation of section 56(c) of the Mineral and Petroleum Resources Development Act 28 of 2002 (MPRDA) and section 73(6A) of the Companies Act 61 of 1973. According to section 56(c) of the MPRDA, rights to minerals lapse when a company is deregistered. Section 73(6A) of the 1973 Companies Act provides an opportunity for a company that was deregistered for failing to submit annual returns to be restored to the companies register. According to the Supreme Court of Appeal (SCA), the restoration of a company according to section 73(6A) constitutes a “Biblical Lazarus moment” (par 5 and 12) for a prospecting right that lapsed according to section 56(c) of the MPRDA: upon restoration of the company, the prospecting right miraculously revives from the dead. In this case discussion, we investigate whether the revival of rights to minerals in the manner allowed in the Palala case accords with the objectives of the MPRDA. We specifically investigate the correct interpretation of section 56(c) of the MPRDA in the particular circumstances of the case, namely, when companies that hold prospecting rights are deregistered for failing to submit annual returns. Although not discussed here, our arguments can be extended to all rights to minerals and to all scenarios envisaged in section 73 of the 1973 Companies Act; i.e., where companies are removed from the register without being wound up. Our arguments do not cover the voluntary or involuntary winding up of solvent companies (s 80 and 81 of the Companies Act 71 of 2008 (the 2008 Companies Act)) or the winding up of insolvent companies (s 344 of the 1973 Companies Act). At all material times during the dispute, the 1973 Companies Act, and not the 2008 Companies Act, was operational. We compare the position in the 2008 Companies Act throughout the discussion.